2016
DOI: 10.1111/eci.12608
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic implication of slug in all tumour patients – a systematic meta‐analysis

Abstract: The protein expression rather than mRNA transcription of Slug should be considered as a potent biomarker for poor prognosis of tumours, particularly head and neck cancer as well as lung and urinary carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Accumulating evidence has demonstrated that these EMT‐TFs are associated with invasion and metastasis in HNSCC . In our previous studies, we found that ZEB2 and SNAI2 enhanced the invasive and metastatic capability of HNSCC cells and their expression was correlated with a poor prognosis, which was also confirmed by several other studies . However, a comprehensive pooled analysis investigating the prognostic value of EMT‐TFs in HNSCC was still lacking.…”
Section: Discussionsupporting
confidence: 74%
“…Accumulating evidence has demonstrated that these EMT‐TFs are associated with invasion and metastasis in HNSCC . In our previous studies, we found that ZEB2 and SNAI2 enhanced the invasive and metastatic capability of HNSCC cells and their expression was correlated with a poor prognosis, which was also confirmed by several other studies . However, a comprehensive pooled analysis investigating the prognostic value of EMT‐TFs in HNSCC was still lacking.…”
Section: Discussionsupporting
confidence: 74%
“…These proteins are responsible for downregulating E-cadherin and activating traits leading to the upregulation of mesenchymal markers, additionally influencing apoptosis, angiogenesis, and cell migration (86)(87)(88). The overexpression of each of these transcription factors has been confirmed to have a negative prognostic significance in most common epithelial cancers (88)(89)(90). In our study, we observed an elevated SNAIL, SLUG, and Twist1 immunoreactivity in NSCLC compared to NMLT samples, which is in line with previous literature reports (91)(92)(93).…”
Section: Discussionsupporting
confidence: 92%
“…Another major limitation of this study is that the results have not yet been validated with an independent data set [7] and should therefore be considered preliminary. It should finally be noted that in contrast to univariate [56] or genomic analyses [57], Slug IHC status was not prognostic in this multivariable analysis (p = 0.13; Figure 5; Table S3).…”
Section: Discussionmentioning
confidence: 62%